Pengembangan Media Game Petualangan Geomat Berbasis Adobe Flash untuk Meningkatkan Hasil Belajar Siswa Kelas 5 SD - Theo Hendratta Putra; Mawardi Mawardi (Jurnal Bidang Pendidikan Dasar, 2021)
The demands of 21st-century learning emphasize primary school teachers and students to have adequate skills, creativity, innovation following global dynamics. To meet the demands of 21st-century learning, the purpose of this study is to develop learning media for the game "Geomat's Adventure" to improve learning outcomes for grade 5 elementary school students. This study uses the Research and Development (R&D) type of research. The results of the material validation obtained a score of 66%, including in the interval 61-80% with the high category. Validation of the learning design obtains a score of 80% in the 61-80% interval getting the high category. Media validation obtained a score of 94.2%, including in the 81-100% interval, the category was very high. The findings of the validation results from material experts and learning media become a reference that media products so that in making Geomat's Adventure it is feasible to be used.